2016
DOI: 10.1007/s10840-016-0179-5
|View full text |Cite
|
Sign up to set email alerts
|

Repeat procedures after second-generation cryoballoon ablation as an index procedure for persistent atrial fibrillation: one-year follow-up

Abstract: Our findings show that repeat ablation procedures following a second-generation cryoballoon ablation for persistent atrial fibrillation result in 75 % of freedom from any atrial tachycardia at 12 months follow-up. Of the recurrences, 63 % were due to new onset of atrial fibrillation and 37 % to organized tachycardias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…If patients have recurrent AF after PVI, a second ablation is often pursued. FFAF after pulmonary vein reisolation (PVRI) remains suboptimal at 40% to 75%, with lower rates of FFAF if patients have nonparoxysmal atrial fibrillation (NPAF) before PVRI 4‐7 . There are limited data to guide ablation technique in patients who have recurrent AF after PVI 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…If patients have recurrent AF after PVI, a second ablation is often pursued. FFAF after pulmonary vein reisolation (PVRI) remains suboptimal at 40% to 75%, with lower rates of FFAF if patients have nonparoxysmal atrial fibrillation (NPAF) before PVRI 4‐7 . There are limited data to guide ablation technique in patients who have recurrent AF after PVI 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…Since atrial flutter can occur following PVI, it is important to understand the pattern of post-CBA-PVI atrial flutter [6]. There are limited data describing the incidence and intracardiac origin of atrial flutters following CBA-PVI [7,8]. One smaller study of routine rhythm monitoring after first-time CBA-PVI found the post-CBA-PVI atrial flutter incidence as confirmed by EPS is 5.6% (4 of 181 patients) with mean follow-up 16.6 months.…”
Section: Introductionmentioning
confidence: 99%